Estrategias didácticas constructivistas para el fortalecimiento del rendimiento académico en Química. Año lectivo 2022-2023 - Méndez Jiménez, Jefferson Alberto (2023)
The application of constructivist didactic strategies, promotes students’ participation, in such a way they build significant learning and there is an improvement in their academic record, which is why the present research was carried out in order to strengthen the academic performance of the students of the first year of baccalaureate of “La Porciúncula High school” in the subject of Chemistry. The purpose of this curricular research is, to strengthen the academic performance of students of the first year of the educative institution, through the application of constructivist didactic strategies in the subject of Chemistry of “La Porciúncula” private Educative Unit, in the school year 2022 – 2023. Seeking to achieve what was proposed, the type of qualitative research was used, which allowed to determine relevant characteristics of the educational environment, referring to the application of constructivist didactic strategies to improve the academic performance of students. The research approach corresponds to participatory action research, resulting in a significant improvement in the teaching and learning process. The work carried out together with students and teachers has allowed to motivate the active participation of the learners and therefore the improvement in their academic performance, thanks to the management of constructivist didactic strategies with their respective techniques and resources. Likewise, the design, due to its temporality was transversal. In order to demonstrate its validation, measurement scales called aptitudes or satisfaction were applied. The achieved results denote a considerable improvement in terms of the achievement of significant learning in students, and at the same time the improvement of their academic performance as a consequence of the application of the intervention proposal, through the use of constructivist strategies with their pertinent techniques and didactic resources in accordance to the teaching topics. Key words: Teaching and learning process, Academic record, Significative learning, Students’ participation.